Antioxidant and cytokine modulation in PCOS rats protected with probiotics, myo-inositol, and herbal extracts - AA Zaki; NM Alharbi; TI Almundarij; SM Albarrak (Veterinární Medicína)
This study investigated the pathophysiology of polycystic ovarian syndrome (PCOS) and evaluated the protective effects of various treatments in immature female Wistar rats (N = 48). The rats were divided into 6 groups: Olive oil injection (negative control, G1); testosterone propionate (TP)-induced PCOS (G2); probiotic + TP (G3); myo-inositol (myo-ins) + TP (G4); U. dioica extract + TP (G5); W. somnifera extract + TP (G6). The body weight, body weight gain, and percentage gain were measured weekly and then transformed using the base-10 logarithm (log10). TNF-α, IL-4, IL-10, and IL-17 were weekly measured using ELISA kits. Glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), and catalase (CAT) were analysed in the serum and liver extracts. The W. somnifera significantly reduced the TNF-α levels (P < 0.01). The probiotic and myo-ins significantly elevated the IL-10 levels (P < 0.01). Both plant extracts moderately restored the IL-10 levels. The probiotic and U. dioica administration significantly reduced the IL-17 levels (P < 0.01). The W. somnifera administration also decreased the IL-17 levels, though the effect was less pronounced than that of U. dioica. The probiotic, myo-ins, and W. somnifera groups exhibited enhanced CAT activity (P < 0.05). W. somnifera showed significant increases in the SOD and GSH-Px activities (P < 0.01), showing the most dramatic improvement. The use of these four treatments as a monotherapy in this study resulted in different changes. Therefore, further investigation is necessary to evaluate the protective effects of combining duos or trios of these treatments against this disease.